Efficiency of ozone compared to commercial sanitizers for hatching eggs from older breeders - Souza , Leticia Cardoso; Silva Junior, Joel Lima da; Rufino, João Paulo Ferreira; Nazaré, Sebastião Corrêa de; Mendonça, Marco Antonio de Freitas (Acta Scientiarum. Animal Sciences, 2024)
This study aimed to evaluate the potential of ozone as a sanitizer compared to commercial sanitizers for hatching eggs stored in hatching machines using different turning systems. The eggs (n = 120) were distributed in a completely randomized design using a factorial scheme (6x2) where the treatments were constituted by different sanitizers applied (non-treated eggs, Ozone 1.6 mg L-1, Ozone 3.2 mg L-1, Cyphenothrin, UVC, and paraformaldehyde) and two turning systems (vertical and horizontal) with 10 eggs each, with the egg considered as a replicate. Data collected were subjected to the Tukey test at 0.05. We observed a very similar performance in the incubation yield results of the hatching machines with different turning systems, where the hatching percentage of eggs stored in the hatching machine using vertical turning presented better (p < 0.05) results. Comparing ozone to other sanitizers, we observed that paraformaldehyde and UVC provided better (p < 0.05) hatching percentage. However, both ozone concentrations used also presented good hatching percentage results. Chicks from treated eggs, except those from eggs treated with the highest ozone concentration (3.2 mg L-1), were heavier (p < 0.05) at hatch. Chicks from eggs treated with the low concentration of ozone (1.6 mg L-1) presented, in several scenarios, higher (p < 0.05) weight at hatch than chicks from eggs treated with sanitizers commonly used, especially paraformaldehyde and UVC. Conclusively, ozone can be used as a sanitizer to treat eggs from older breeders, presenting potential to replace commonly used sanitizers stored in hatching machines using both vertical and horizontal turning systems.